If it does not move me, it does not belong to me: challenges to teacher education in a global and sustainable perspective - de Almeida Pimenta, Maria Alzira; Prata-Linhares, Martha; Bonventi Júnior, Waldemar (Lumina, 2018)
In these first years of the millennium, schools in Brazil and around the world have faced great challenges. Including: complex social circumstances (large scale population migration), the arrival of the Internet providing fast access to every type of information and the exclusion of the population that is not connected, appreciation of knowledge as a factor of production, the appeal for consumerism and the need for principles and practices that give value to diversity and sustainability. Added to this, is the resistance of these institutions regarding change, and the powers of persuasion of the media as inductive of behaviors and desires. However, we think that the primary material for the necessary transformations is in the school itself. In it, and from it, will changes be generated and implemented. Based on data collected, in eight countries, carried out with university teachers and students of courses for the development of teachers, analysis and reflections will be presented which highlight the role of the education institutions in the necessary transformations and suggestions for the implemented changes.